Problem-Solving and working memory in children - mohammadhosein abdollahi (Muṭāli̒āt-i Ravān/Shināsī-i Bālīnī, 2018)
The aim of this study was to investigate the effectiveness of the training of emotional competence in the improvement of anxiety, problem solving and working memory in children. It was a semi experimental research in which pre- test, post -test design with control group was used. Through the cluster sampling method 30 female children were selected from the primary schools of Babol city and then they were randomly put into two experimental and control groups. The assessment was performed using Multi-dimensional Children's Anxiety Scale (MASC), Social Solution Scheduler (SPSI-R) and Dunnian and Carpenter Working Memory Test (1980). The experimental group received an emotional competence training program based on two, EBP emotion-based prevention programs (Izard et al2004, 2008) and Cole's emotional knowledge intervention (2009), adapted from Hesarsorkhi (1395), for 10 group sessions for 60 minute. There was no intervention in the control group. The results of one-variable and multivariate covariance analysis showed that there is a significant difference between the experimental group and control group in the post-test in anxiety score constructive problem solving and memory working in the children. The results of this study showed that emotional competence training program can be an effective way to reduce anxiety and increase the ability of constructive problem solving, working memory of children.